A Predictive Model of Adversity Quotient: The Contribution of Self-Efficacy and Social Support among Toraja Fresh Graduates - Yen Chorina; Susana Prapunoto; Sutarto Wijono (Kuras Institute, 2026)
Recent graduates face significant challenges during the transition to the workforce, which requires a strong adversity quotient (AQ). The purpose of the study is to evaluate social support and self-efficacy as determinants of recent graduates in Toraja, South Sulawesi. This study employed a quantitative correlational research design. The population consisted of fresh graduates residing in Toraja, with a total sample of 196 participants. Data were collected using the Adversity Quotient Scale, the General Self-Efficacy Scale, and the Multidimensional Scale of Perceived Social Support. Multiple linear regression analysis was conducted to test the simultaneous predictive effects of self-efficacy and social support on adversity quotient. The findings revealed that self-efficacy and social support simultaneously and significantly predicted the adversity quotient of fresh graduates. Both variables showed positive contributions, indicating that higher levels of self-efficacy and perceived social support were associated with higher levels of adversity quotient. These results underscore the combined importance of internal belief systems and external support networks in enhancing resilience among fresh graduates. The study provides empirical evidence from a specific regional context and highlights the need for interventions that strengthen both personal competence and social support systems during the transition to the workforce.